Answer:
x=3
Step-by-step explanation:
5х - 2 = 3х + 4
5х - 3х = 4 + 2
2х = 6
х = 6/2
х = 3
Hope this helps!
Answer:
117 degrees
Step-by-step explanation:
theres no picture and not alot of context so i just subtracted 180 and 63
Answer:
Using trigonometric ratio:
![\sec \theta = \frac{1}{\cos \theta}](https://tex.z-dn.net/?f=%5Csec%20%5Ctheta%20%3D%20%5Cfrac%7B1%7D%7B%5Ccos%20%5Ctheta%7D)
![\tan \theta = \frac{\sin \theta}{\cos \theta}](https://tex.z-dn.net/?f=%5Ctan%20%5Ctheta%20%3D%20%5Cfrac%7B%5Csin%20%5Ctheta%7D%7B%5Ccos%20%5Ctheta%7D)
From the given statement:
and sin < 0
⇒
lies in the 3rd quadrant.
then;
![\sec \theta = \frac{1}{-\frac{4}{5}} = -\frac{5}{4}](https://tex.z-dn.net/?f=%5Csec%20%5Ctheta%20%3D%20%5Cfrac%7B1%7D%7B-%5Cfrac%7B4%7D%7B5%7D%7D%20%3D%20-%5Cfrac%7B5%7D%7B4%7D)
Using trigonometry identities:
Substitute the given values we have;
![\sin \theta = \pm\sqrt{1-(\frac{-4}{5})^2 } =\pm\sqrt{1-\frac{16}{25}} =\pm\sqrt{\frac{25-16}{25}} =\pm \sqrt{\frac{9}{25} } = \pm\frac{3}{5}](https://tex.z-dn.net/?f=%5Csin%20%5Ctheta%20%3D%20%5Cpm%5Csqrt%7B1-%28%5Cfrac%7B-4%7D%7B5%7D%29%5E2%20%7D%20%3D%5Cpm%5Csqrt%7B1-%5Cfrac%7B16%7D%7B25%7D%7D%20%3D%5Cpm%5Csqrt%7B%5Cfrac%7B25-16%7D%7B25%7D%7D%20%3D%5Cpm%20%5Csqrt%7B%5Cfrac%7B9%7D%7B25%7D%20%7D%20%3D%20%5Cpm%5Cfrac%7B3%7D%7B5%7D)
Since, sin < 0
⇒![\sin \theta = -\frac{3}{5}](https://tex.z-dn.net/?f=%5Csin%20%5Ctheta%20%3D%20-%5Cfrac%7B3%7D%7B5%7D)
now, find
:
![\tan \theta = \frac{\sin \theta}{\cos \theta}](https://tex.z-dn.net/?f=%5Ctan%20%5Ctheta%20%3D%20%5Cfrac%7B%5Csin%20%5Ctheta%7D%7B%5Ccos%20%5Ctheta%7D)
Substitute the given values we have;
![\tan \theta = \frac{-\frac{3}{5} }{-\frac{4}{5} } = \frac{3}{5}\times \frac{5}{4} = \frac{3}{4}](https://tex.z-dn.net/?f=%5Ctan%20%5Ctheta%20%3D%20%5Cfrac%7B-%5Cfrac%7B3%7D%7B5%7D%20%7D%7B-%5Cfrac%7B4%7D%7B5%7D%20%7D%20%3D%20%5Cfrac%7B3%7D%7B5%7D%5Ctimes%20%5Cfrac%7B5%7D%7B4%7D%20%3D%20%5Cfrac%7B3%7D%7B4%7D)
Therefore, the exact value of:
(a)
![\sec \theta =-\frac{5}{4}](https://tex.z-dn.net/?f=%5Csec%20%5Ctheta%20%3D-%5Cfrac%7B5%7D%7B4%7D)
(b)
![\tan \theta= \frac{3}{4}](https://tex.z-dn.net/?f=%5Ctan%20%5Ctheta%3D%20%5Cfrac%7B3%7D%7B4%7D)
Answer: 3/2
Step-by-step explanation:
3/10 * 5
3/10 * 5/1
this can be simplified, the 5 cancels out and the 10 becomes a 2
3/2*1/1 = 3/2
Answer:
(0, 1 ) and (
,
)
Step-by-step explanation:
Given the 2 equations
x³ - xy = 0 → (1)
x + y = 1 → (2) ( subtract x from both sides )
y = 1 - x → (3)
Substitute y = 1 - x into (1)
x² - x(1 - x) = 0
x² - x + x² = 0
2x² - x = 0 ← factor out x from each term on the left side
x(2x - 1) = 0
Equate each factor to zero and solve for x
x = 0
2x - 1 = 0 ⇒ 2x = 1 ⇒ x = ![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
Substitute these values into (3) for corresponding values of y
x = 0 : y = 1 - 0 = 1 ⇒ (0, 1 )
x =
: y = 1 -
=
⇒ (
,
)